Supported Planar Bilayers for the Formation of Study of Immunological Synapses and Kinapse. - Vardhana, S; Dustin, M (2008)
Supported planar bilayers are powerful tools that can be used to model the molecular interactions in an immunological synapse. To mimic the interactions between lymphocytes and antigen presenting cells, we use Ni2+-chelating lipids to anchor recombinant cell adhesion and MHC proteins to the upper leaflet of a bilayer with poly-histidine tags. Planar bilayers are generated by preparing lipid, treating the glass surfaces where the bilayer will form, and then forming the bilayer in a specialized chamber containing a flow-cell where the lymphocytes will be added. Then, bilayers are charged with Ni and his-tagged recombinant proteins are added. Finally, lymphocytes are injected into the flow cell and TIRF microscopy can be used to image synapse formation and the mechanisms that control T cell locomotion, sites of receptor sorting, and sites of receptor degradation.